2016
DOI: 10.1007/s13277-016-5433-z
|View full text |Cite
|
Sign up to set email alerts
|

PI3K and MAPK pathways mediate the BDNF/TrkB-increased metastasis in neuroblastoma

Abstract: Brain-derived neurotrophic factor (BDNF) and its tyrosine kinase receptor TrkB have been reported to be associated with poor prognosis in neuroblastoma (NB) patients. Our previous studies indicated that BDNF activation of TrkB induces chemo-resistance through activation of phosphoinositide-3-kinase (PI3K)/Akt pathway. In this study, we investigated the role of BDNF/TrkB on metastasis in NB. A tetracycline-regulated TrkB-expressing NB cell line (TB3) was used. Scratch wound healing assay, Boyden chamber migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 41 publications
3
38
1
Order By: Relevance
“…Furthermore, our observation of a strong association between melanoma metastasis and BDNF immunopositivity is consistent with the report of more frequent expression of BDNF and TrkB in metastatic lesions compared to primary lesions by Innominato et al [22], and further supports the hypothesis that BDNF activation of TrkB receptor signaling promotes neuroblastoma metastasis via PI3K/Akt/mTOR and MAPK pathways [23]. Regarding the mitotic index, we found that a higher index was associated with the presence of TrkA and NGF immunoreactivity.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our observation of a strong association between melanoma metastasis and BDNF immunopositivity is consistent with the report of more frequent expression of BDNF and TrkB in metastatic lesions compared to primary lesions by Innominato et al [22], and further supports the hypothesis that BDNF activation of TrkB receptor signaling promotes neuroblastoma metastasis via PI3K/Akt/mTOR and MAPK pathways [23]. Regarding the mitotic index, we found that a higher index was associated with the presence of TrkA and NGF immunoreactivity.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, BDNF has been shown to promote non-small lung cancer proliferation in an autocrine manner and metastasis of neuroblastoma through STAT3 and PI3K and MAPKsingalling pathway, respectively [21, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that TTM‐induced phase shifts require activation of TrkB receptors, similar to glutamate‐induced phase shifts (Mou et al., ; Yamada & Prosser, ). TrkB is known to activate PI3k/AKT signaling as well as MAPK/ERK signaling (Hua et al., ; Marsden, ; Van't Veer et al., ; Yoshii & Constantine‐Paton, , ; Zhou et al., ). As TTM‐induced phase shifts were not blocked by inhibition of MAPK or NO signaling cascades, we used the PI3K/Akt inhibitor, LY294002, to test whether the PI3K/Akt signaling pathway is involved in TTM‐induced phase shifts (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to reiterate that the effects of Cu, even across physiological (low micromolar) concentrations, appear to vary dramatically across brain regions and cell type (Doreulee et al., ; Shcheglovitov et al., ; Marchetti et al., ; Maureira et al., ; Hu, Ni, Duff‐Canning, & Wang, ; Kapkaeva et al., ). Moreover, while decreases in Cu levels can increase excitotoxicity as mentioned above, higher levels of exogenous Cu can also decrease cell viability through oxidative stress‐linked processes (Hua et al., ; Kapkaeva et al., ). Interestingly, SCN neurons are robustly resistant to glutamate excitotoxicity, and ERK1/2 signaling in SCN tissue has been reported to be neuroprotective against excess glutamate (Bottum, Poon, Haley, Karmarkar, & Tischkau, ; Karmarkar, Bottum, Krager, & Tischkau, ).…”
Section: Discussionmentioning
confidence: 99%